The Youth Generation’s Lens: Exploring Gender Issues in Italian Networks of Public Debates on the European Union - Parito, Mariaeugenia; Pasciuto, Fabrizia (SocietàMutamentoPolitica, 2025)
The paper aims to analyse if gender equality is a relevant issue for young Italians involved in European networks of debates, enhanced by social media, and committed in participatory practices to mobilise others to raise awareness towards European integration, policies and values. An exploratory qualitative research was carried out in the light of the 2024 European election, using in-depth semi-structured interviews conducted between March and May 2024. Some interesting results emerge.Young activists recognise gender equality as value and a human right at the core of the EU democracy and they perceive efforts to address gender equality as a challenge essential for shaping an European society characterised by social justice, inclusivity and human dignity. Nevertheless, the interviewees show a pragmatic stance, evaluating the importance for tackling gender disparities but questioning the effectiveness of the European strategies, in particular their ability to effectively influence national-level decision-making. Some limitations should be noted, in particular further research should explore the relationship between political perspective, education and values orientations.